Cementoenamel Junction: Morphological Characterization in Nepali Population - Adhikari, Bhoj Raj; Shakya, Mamata; Poudel, Pratibha; Rijal, Arjun Hari; Lamichhane, Simant; Mahanta, Swagat Kumar; Upadhyay, Chandan; Humagain, Manoj (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Cementoenamel junction (CEJ) represents the anatomic limit between the crown and root surface and is defined as the area of the union of the cementum and enamel at the cervical region of the tooth. However, the type of CEJ in the Nepali population is not well documented. Objective: In the present study, the authours attempt to characterize the morphological type of CEJ in the Nepali population. Methods: This is a descriptive cross-sectional study using a total of 300 CEJs from the Nepali population visiting the Kathmandu University School of Medical Sciences, Department of Dental Surgery, Dhulikhel Hospital (KUSMS-DH) between January 2023 to August 2023. Extracted teeth were sectioned to 250μm thickness and observed under the light microscope to determine the type of CEJ. Results: Most of the samples presented type I CEJ. Type I, II, and III CEJ were seen in 149 (49.67%), 103 (34.33%), and 48 (16%) of the samples respectively. Additionally, 110 (73.34%) of the samples showed similar types of CEJ in both the buccal and palatal sides of the same tooth while 40 (26.66%) had different types of CEJ within the same tooth. Conclusions: Type I CEJ is the most common in the Nepalese population. The type of CEJ shows variation within the same teeth in different areas.